KOMUNIKASI POLITIK PEREMPUAN: Studi Dramaturgis Komunikasi Politik Perempuan Di DPRD Jawa Barat - Zaenal Mukarom (Indonesian Journal of Dialectics, 2012)
The purpose of this research was to learn more regards: (1) the preparation of women politicians before excecuting their duties as parlimentiary members in order to implement the legislation, controlling and budgeting functions; (2) The performance of  women politicians involving their duties to execute the legislation, controlling and budgeting functions; and (3) The perception of men politicians on women politicians in their execution of legislation, controlling and budgeting functions.            Methods used in this research was qualitative (subjective’s perspective) with simbolic paradigm and dramaturgy as its variance. The data collection methods used in this research were interview, observation and documentation.The result of this research indicates that (1) In the preparation of women politicians before excecuting their duties as parlimentiary, there wasa synergy pattern development among one stage with another stages. This development include motivation stage, deepening subject material stage and consultation stage; (2) The performance of  women politicians whenexcecuting their duties: legislation, controoling and budgeting functions generally less than optimal comparedto men politicians. This conclusion was based on some constraints that  women politicians have to face, such as economics, culture, background and experience life in politics, and (3) The perception of men politicians on women politicians in their execution of legislation, controlling and budgeting functions some are still gender bias. In the other words  men politicians were still underestimate the competence and capacity of women politicians in their capacity as perlimeantary member. Nevertheles, men politicians generally stated that they  agreed to positioning women politicians as their partner in carrying out the functions of legislation, controlling and budgeting in West Java Parliament. Therefore, according to the perception of men politicians, the efforts to increase the capacity, competence and quality of women politicians have to be improved either through political education with gender literacy through the support of a number of regulations that provide protection against the participation and political rights of women.